The understanding and implementation of Religious Moderation and national insight by Islamic student movements - Harimurti, Shubhi Mahmashony (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2023)
This research aims and has objectives of the research to analyze the understanding and implementation of the Islamic student university movement to the concept of Religious Moderation and national insight. This research was conducted at the office of the Muhammadiyah Student University Association (IMM) and Indonesian Muslim University Students Action Association (KAMMI) UGM which were the samples in this research. The research method used field research and literature. Field research by interviewing and filling out questionnaires while literature as a secondary source to strengthen primary data. It was found that the understanding of KAMMI UGM cadres was better than IMM UGM on these two issues. It can be concluded that a good understanding of Religious Moderation and national insight is not directly in line with its implementation. Another finding from this study is that a good understanding of Religious Moderation is not directly in line with the knowledge of the cadres of the Islamic student movement about national insight.